A portrait of intimate apparel female shoppers: A segmentation study. Issue 1 (February 2017) - Tsarenko, Yelena; Lo, Carolyn J.
Highlights: Bra style and design remain critical factors across segments regardless of involvement levels. Lingerie brands are important for highly involved Enthusiasts, but less so for Dilettantes and Pragmatists . Moderately involved Dilettantes are less competent in bra shopping but exhibit high product interest. Competent Enthusiasts indicate preference for fitting services, suggesting need for assurance and choice affirmation. Hedonic pleasure in bra shopping appears to decline with age while purchase competency increases Abstract: This research expands dialogue on the dynamic consumer–product relationship within the under-researched, albeit sensitive, context of intimate wear. Drawing on involvement theory alongside specific product and service attributes, this study delineates and profiles segments within the highly engendered consumption of the bra. Data gathered from 221 Australian females unveiled three distinct segments of female bra shoppers: Enthusiasts who derive significant hedonic value in purchasing bras, Dilettantes who portray high interest in lingerie but exhibit the lowest levels of competency in bra-shopping, and Pragmatists who hold the lowest score in terms of hedonic value but perceive themselves as highly competent bra shoppers. Demographic and attribute profiling further captures differences between segments on factors including age, brand importance, lingerie servicescape ambience, and professional fitting advice. Findings provide relevant insights for lingerie retailers and suggestions for future research. Chinese Abstract: 该项研究将消费者与产品之间动态关系的对话扩展到亟待研究的敏感领域——内衣消费。 该项研究根据涉入理论并结合特定产品属性和服务属性, 描述和介绍了高消耗文胸的细分市场。 来自 221 名澳大利亚女士的数据揭示了女性文胸购买者的三个不同细分市场：热衷者通常能从购买文胸中满足其享乐主义价值观, 而外行的购买者通常对内衣表现出高昂的兴趣, 但是在购买文胸时却表现出极低的购买力, 而实用主义者并不能从购买体验中获得享乐价值, 但是她们认为自己是最具购买力的文胸购买者。 人口统计学和产品属性与服务属性分析进一步反映了细分市场之间的区别, 包括年龄、品牌重要性、内衣服务环境和专业试衣建议相关因素对细分市场的影响。 这些发现为内衣零售商提供了相关的见解, 并对未来研究的方向提出了建议。